Ejercicios excéntricos en la prevención de lesiones isquiotibiales en futbolistas - Pazmiño Patiño, José Daniel (2023)
ABSTRACT: The present study was developed under the modality of literature review entitled eccentric exercises in the Prevention of hamstring injuries in Soccer Players, belonging to the research line of health in physical rehabilitation. A hamstring injury is generally an overstretching of the myotendinous junction, the biceps femoris, the muscle most prone to injury. These injuries are usually caused by non-contact mechanisms and frequently occur in the terminal swing phase of a sprint due to the high quality of demand that this sport requires. Being the most frequent diagnosis in soccer and characterized by a high rate of recurrence, injury prevention programs, such as eccentric exercises, are necessary in this region. For the research process, information collection was based on scientific property arguments. To acquire various sources of accurate information, scientific reference bases were used, such as PubMed, Google Scholar, Scielo, Elsevier, and Science Direct, among others of academic interest, using the analytical method that, through the PEDro scale, every one of them was evaluated, filtering inclusion and exclusion criteria, 35 articles that provided a solid evidence base due to their validity. Finally, after concluding the compilation of scientific articles, the effectiveness of eccentric exercise in preventing hamstring injuries in soccer players has been demonstrated, primarily through the use of the Nordic Hamstring Exercise. The results obtained regarding strength and its variables, Maximum Eccentric Torque, and H/Q Ratio are inconclusive.